Scapular bracing and alteration of posture and muscle activity in overhead athletes with poor posture - Cole, A. K.; McGrath, M. L.; HarringtonS. E.; Padua, D. A.; Rucinski, T. J.; Prentice, W. E. (Journal of Athletic Training, 2013)
Context: Overhead athletes commonly have poor posture. Commercial braces are used to improve posture and function, but few researchers have examined the effects of shoulder or scapular bracing on posture and scapular muscle activity. Objective: To examine whether a scapular stabilization brace acutely alters posture and scapular muscle activity in healthy overhead athletes with forward-head, rounded-shoulder posture (FHRSP). Design: Randomized controlled clinical trial. Setting: Applied biomechanics laboratory. Patients or Other Participants: Thirty-eight healthy overhead athletes with FHRSP. Intervention(s): Participants were assigned randomly to 2 groups: compression shirt with no strap tension (S) and compression shirt with the straps fully tensioned (S + T). Posture was measured using lateral-view photography with retroreflective markers. Electromyography (EMG) of the upper trapezius (UT), middle trapezius (MT), lower trapezius (LT), and serratus anterior (SA) in the dominant upper extremity was measured during 4 exercises (scapular punches, W's, Y's, T's) and 2 glenohumeral motions (forward flexion, shoulder extension). Posture and exercise EMG measurements were taken with and without the brace applied. Main Outcome Measure(s): Head and shoulder angles were measured from lateral-view digital photographs. Normalized surface EMG was used to assess mean muscle activation of the UT, MT, LT, and SA. Results: Application of the brace decreased forward shoulder angle in the S + T condition. Brace application also caused a small increase in LT EMG during forward flexion and Y's and a small decrease in UT and MT EMG during shoulder extension. Brace application in the S + T group decreased UT EMG during W's, whereas UT EMG increased during W's in the S group. Conclusions: Application of the scapular brace improved shoulder posture and scapular muscle activity, but EMG changes were highly variable. Use of a scapular brace might improve shoulder posture and muscle activity in overhead athletes with poor posture.